Understanding Plasma Dynamics of Argentina Nano Focus Machine Using the Lee Code - Arwinder, Singh*; Teh, Thiam Oun; Saw, Sor Heoh; Lee, Sing (Akademi Sains Malaysia, 2022)
Argentina Nano Focus Machine is a small plasma focus machine used as an intense neutron source. To understand the working of its plasma dynamics, the Lee model code is used. The results obtained from the Lee code agree reasonably well with the experimental data in terms of the peak current, radial start time and the pinch duration. Additionally, this code also produces information such as the optimum neutron yield (6.2x104), maximum ion beam energy (1.2 J) and the dependence of these yields and various speeds on operating pressure. The resultant data is reliable and all the input that is required is just one experimental current waveform together with the actual machine and operating parameters